Evaluasi Efektivitas Latihan Beban dengan Model Circuit Weight Training Terhadap Perbaikan Indeks Massa Tubuh - Warthadi, Anugrah Nur; Kurniawan, Ardhian Tomy; Khoirurrozikin , Akhmad Azlan (Universitas Hamzanwadi, 2024)
This study aims to measure the effectiveness of circuit weight training (CWT) in improving the body mass profile of guns gym Surakarta members. The research used was quasi-experimental with pretest posttest design. The population amounted to 35 people and a sample of 10 met the criteria. Data collection conducted in this study using measurement tests. Changes in body mass profile were assessed through three main indicators, namely body weight, body circumference size, and body fat content, to calculate body mass index (BMI) before and after following the exercise program. Data processing using paired sample t test showed a decrease in mean BMI from 26.52 to 26.11, with a decrease of 0.407. The significance value of 0.000 (p < 0.05) indicates a positive and significant effect of circuit weight training on improving body composition. The results of this study prove that circuit weight training is effective in improving body composition and helping to achieve a more ideal body weight. This study also highlights the importance of a purposeful exercise program in supporting improvements in overall fitness and health. It was concluded that circuit weight training is effective in improving the body mass profile of fitness members at guns gym compared to before the training program was conducted.